Effectiveness of drug repurposing and natural products against SARS-CoV-2: A comprehensive review (2024)
ABSTRACT: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a betacoronavirus responsible for the COVID-19 pandemic, causing respiratory disorders, and even death in some individuals, if not appropriately treated in time. To face the pandemic, preventive measures have been taken against contagions and the application of vaccines to prevent severe disease and death cases. For the COVID-19 treatment, antiviral, antiparasitic, anticoagulant and other drugs have been reused due to limited specific medicaments for the disease. Drug repurposing is an emerging strategy with therapies that have already tested safe in humans. One promising alternative for systematic experimental screening of a vast pool of compounds is computational drug repurposing (in silico assay). Using these tools, new uses for approved drugs such as chloroquine, hydroxychloroquine, ivermectin, zidovudine, ribavirin, lamivudine, remdesivir, lopinavir and tenofovir/emtricitabine have been conducted, showing effectiveness in vitro and in silico against SARS-CoV-2 and some of these, also in clinical trials. Additionally, therapeutic options have been sought in natural products (terpenoids, alkaloids, saponins and phenolics) with promising in vitro and in silico results for use in COVID-19 disease. Among these, the most studied are resveratrol, quercetin, hesperidin, curcumin, myricetin and betulinic acid, which were proposed as SARSCoV-2 inhibitors. Among the drugs reused to control the SARS-CoV2, better results have been observed for remdesivir in hospitalized patients and outpatients. Regarding natural products, resveratrol, curcumin, and quercetin have demonstrated in vitro antiviral activity against SARS-CoV-2 and in vivo, a nebulized formulation has demonstrated to alleviate the respiratory symptoms of COVID-19. This review shows the evidence of drug repurposing efficacy and the potential use of natural products as a treatment for COVID-19. For this, a search was carried out in PubMed, SciELO and ScienceDirect databases for articles about drugs approved or under study and natural compounds recognized for their antiviral activity against SARS-CoV-2.